Knowledge on menstruation and menstrual hygiene practices among adolescent girls of selected schools, Chitwan - Neupane, Mamata Sharma; Sharma, Kalpana; Bista, Archana Pandey; Subedi, Subash; Lamichhane, Sandesh (Journal of Chitwan Medical College, 2020)
Background: Menstrual hygiene is very important aspect for adolescent girls and proper menstrual hygiene has not been sufficiently addressed in developing countries including Nepal. This study aimed to assess the knowledge on menstruation and menstrual hygiene practices among adolescent girls.Methods: Descriptive cross-sectional study was conducted among adolescent girls studying in selected schools of Chitwan district. A total 193 girls who had menstrual flow experience for at least three consecutive menstrual cycles were selected as sample using the consecutive sampling technique. Data were analyzed in Statistical Package for Social Sciences (SPSS) version 16.0 using descriptive and inferential statistics.Results: Most of the girls knew about menstruation as physiological process, normal age of menstruation, and causes of menstruation as hormonal change. Overall, 66.8% of girls had adequate level of knowledge on menstruation. Regarding practice, 94.8% cleaned their genitalia properly, 93.8% used the sanitary pads, and 97.4% wrapped and disposed the pads in dustbin after use. Overall, 72.5% of girls had good level of menstrual hygiene practices. Adolescent girl’s age and grade, and occupation status of their father were significantly associated (p < 0.05) with menstrual hygiene practice. Further, significant positive relationship found between knowledge on menstruation and menstrual hygiene practice.Conclusions: One third of adolescent girls have inadequate knowledge on menstruation and one fourth have poor menstrual hygiene practice. Therefore, an awareness and advocacy programs on menstruation and menstrual hygiene practices are needed for the adolescent girls to safeguard themselves against reproductive tract infections.